Котлован: повести, роман / Андрей Платонов ; [послесловие Н. Ивановой] - Платонов Андрей Платонович (Удмуртия, 1989)
Экземпляры: аб. (ретро) / Инвентарный номер: 44787 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 37 / ББК: 84(2Рос=Рус)6